Light emitting diode lamp source with variable colour temperature and intensity - Chng, Nicholas Wen Jun (2018)
In the commercial market, the tunability of white light are limited and usually have only 2 different Correlated Colour Temperature (CCT), I.E. the user can only switch between warm white and cool white. This is possible as the lights source consists of both warm white light emitting diodes (LEDs) and cool white LEDs. Hence by switching, the warm white LEDs and cool white LEDs will be switched on alternatively hence only producing 2 different CCT of white light. In this project, a technique known as colour mixing will be used to generate different CCTs of white light, using monochromatic red, green and blue LEDs. With the varying of the light intensity of each of the LED proportional, white light of different CCT can be achieved. This project will design a circuit that will be able to vary the CCT of the white light produced from the RGB LEDs and vary the intensity to dim the white light as well.